The Course of Alcoholic Cirrhosis of The Liver in a Patient with COVID-19 - E. Y. Kudashkina; L. Y. Ilchenko; I. G. Fedorov (Архивъ внутренней медицины, 2022)
This article presents the features of the course of liver cirrhosis (LC) in a patient with a new coronavirus infection. The patient had no specific respiratory symptoms of COVID-19 (CoronaVirus Disease 2019), and the reason for outpatient examination for SARS-CoV-2 (severe acute respiratory syndrome coronavirus) RNA was the presence of these symptoms in relatives. Previously, patient E. had been undergoing in-patient examination and treatment for abdomen volume build-up against the background of prolonged alcoholization, and was diagnosed with alcoholic class B LC according to Child-Pugh classification. Conservative therapy was administered, and the patient was discharged with regression of ascites. Within a week after SARS-CoV-2 identification, patient E. showed signs of LC decompensation in the form of increasing abdominal volume, which required repeated inpatient treatment, during which portal vein thrombosis (PVT) and progression of chronic liver disease (CLD) in the post-coid period were revealed. Literature data on 30-day mortality in patients with LC against COVID-19 background are presented, as well as my own observations on the example of 580 case histories. Complications of new coronavirus infection in patients with CLD, methods of their correction are considered here. This observation demonstrates the social significance of the problem of COVID-19 incidence in patients with LC, the necessity for screening for COVID-19 in case of the presence of decompensation episodes, as well as active prevention of infection in these patients.